2019
DOI: 10.1080/02673843.2019.1679202
|View full text |Cite
|
Sign up to set email alerts
|

Grit, self-efficacy, achievement orientation goals, and academic performance in University students

Abstract: The current study investigated the relationships between grit, self-efficacy, achievement orientation goals, and academic performance in parallel and serial mediation models. University student participants (N = 258) responded to an online survey containing demographic items and scales measuring the non-cognitive factors noted above. The results demonstrated that 'grit' (i.e. perseverance of effort and consistency of interest) positively associates with academic performance through a sequential pathway of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
256
1
36

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(314 citation statements)
references
References 46 publications
21
256
1
36
Order By: Relevance
“…In contrast, low self-esteem would foster cognitive, affective, and behavioral involvement in the students focused on their social image of competence (either pursuing performance-approach or performance-avoidance goals). To the extent that these goal tendencies usually bring with them significant academic and/or emotional harm for the student [9,12,13,15], low self-esteem is a motivational risk factor.…”
Section: Psycho-educational and Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, low self-esteem would foster cognitive, affective, and behavioral involvement in the students focused on their social image of competence (either pursuing performance-approach or performance-avoidance goals). To the extent that these goal tendencies usually bring with them significant academic and/or emotional harm for the student [9,12,13,15], low self-esteem is a motivational risk factor.…”
Section: Psycho-educational and Health Implicationsmentioning
confidence: 99%
“…In general, there is consensus about the wide range of emotional and academic benefits of adopting learning-approach goals, in contrast to the greater dysfunctionality of avoidance goals-e.g., use of surface learning strategies, poor persistence in the face of difficulties, little help-seeking, burnout, and poor academic performance [9][10][11][12][13][14]. The consequences associated with performance-approach goals, however, have been more controversial, even though it seems that this goal orientation produces adaptive results when the student's objective is to outperform their classmates rather than appear highly competent [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies that examine psycho-emotional variables show that self-efficacy determines an adequate regulation of stress, which is considered positive when it is estimated that the learning goal is achieved with effort [15], and even with positive feelings before the development of the activity when it is supported by mastery and performance objectives [18] and the probability of success is considered [19]. It has been observed that academic self-efficacy is a predictor of academic resilience [20], which is the capacity of students to maintain high motivation and academic performance, even when they are faced with situations of adversity and stress [6].…”
Section: Perceived Academic Self-efficacymentioning
confidence: 99%
“…In fact, self-efficacy is an essential psychological factor influencing achievement, academic motivation, persistence, learning success, and future career choice (Schunk, 1989;Thompson & Verdino, 2018;Webb-Williams, 2018). In another study, Alhadabi and Karpinski (2019) associated low self-efficacy with dishonest academic behavior. In short, this reflects that the experiences of preservice teachers influence their self-efficacy beliefs, thus providing an active learning environment is considered an appropriate way to increase the self-efficacy of graduates (Sahin-Taskin, 2018).…”
Section: Introductionmentioning
confidence: 97%